Index admission cholecystectomy for acute biliary pancreatitis favorably impacts outcomes of hospitalization in cirrhosis. Issue 2 (24th July 2019) - Patel, Kishan P; Mumtaz, Khalid; Li, Feng; Luthra, Anjuli K; Hinton, Alice; Lara, Luis F; Conwell, Darwin L; Krishna, Somashekar G
Abstract: Background and Aim: Despite higher rates of gallstones in patients with cirrhosis, there are no population‐based studies evaluating outcomes of acute biliary pancreatitis (ABP). Therefore, we sought to evaluate the predictors of early readmission and mortality in this high‐risk population. Methods: We utilized the Nationwide Readmission Database (2011–2014) to evaluate all adults admitted with ABP. Multivariable logistic regression models were used to assess independent predictors for 30‐day readmission, index admission mortality, and calendar year mortality. Results: Among 184 611 index admissions with ABP, 4344 (2.4%) subjects had cirrhosis (1649 with decompensation). Subjects with cirrhosis, when compared with those without, incurred higher rates of 30‐day readmission (20.9% vs 11.2%; P  < 0.001), index mortality (2.0% vs 1.0%; P  < 0.001), and calendar year mortality (4.2% vs 0.9%; P  < 0.001). Decompensation in cirrhosis was associated with significantly fewer cholecystectomies (26.7% vs 60.2%; P  < 0.001) and endoscopic retrograde cholangiopancreatographies (23.3% vs 29.9%; P  < 0.001). Multivariate analysis revealed that severe acute pancreatitis (odds ratio [OR]: 14.8; 95% confidence interval [CI]: 5.3, 41.2), sepsis (OR: 12.6; 95% CI: 5.8, 27.4), and decompensation (OR: 3.1; 96% CI: 1.4, 6.6) were associated with increased index admission mortality. Decompensated cirrhosis (OR: 1.8; 95% CI: 1.1, 3.0) and 30‐day readmission (OR: 5.6; 95% CI: 3.3, 9.5) were predictors of calendar year mortality. However, index admission cholecystectomy was associated with decreased 30‐day readmissions (OR: 0.6; 95% CI: 0.4, 0.7) and calendar year mortality (OR: 0.44; 95% CI: 0.25, 0.78). Conclusions: The presence of cirrhosis adversely impacts hospital outcomes of patients with ABP. Among modifiable factors, index admission cholecystectomy portends favorable prognosis by reducing risk of early readmission and consequent calendar year mortality.